CHARACTERIZATION OF MUNDAR PERICARP (Garcinia forbesii) EXTRACT FROM BANJAR DISTRICT OF INDONESIA - Rizki, Muhammad Ikhwan; Triyasmono, Liling; Alfandani, Gina; Hadiah Akbar, Nabila; Khumaira Sari, Anna (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The mundar plant (Garcinia forbesii) is a typical fruit of South Kalimantan. The people use mundar empirically as a spice, cosmetic, and medicine. The purpose of this study was to determine the characteristics of mundar extract from Karang Intan and Beruntung Baru districts in Banjar Regency. The collection of plants from two places, plant determination, and extraction with 70% ethanol. The extract was then characterized. The characterization showed that the Garcinia forbesii pericarp extract from both places was dark brown, distinctive odor, sour taste, and thick. Both extracts contained flavonoids, phenolics, tannins, saponins, glycosides, and anthraquinones. The chromatography of both extracts was the same and detected to alpha-mangosten. The extract from Karang Intan district has a yield 59.99%, total phenolic content 0.888%, moisture content 9.78%, total ash content 1.10%, and acid insoluble ash content 0.06%. The extract from Beruntung Baru district has a yield 58.74%, total phenolic content 0.823%, moisture content 9.93%, total ash content 1.59%, and acid insoluble ash content 0.04%. Garcinia forbesii pericarp extracts from from two places have the same organoleptical characteristics, phytochemical compounds, and chromatography patterns. The differences are in yield percentage, total phenolic content, water content, ash content, and acid insoluble ash content.